Increased Blood Flow Velocity in Middle Cerebral Artery and Headache Upon Ingestion of Ice Water - Hensel, Ole; Burow, Philipp; Mages, Stephan; Wienke, Andreas; Kraya, Torsten; Zierz, Stephan (Frontiers in Neurology, 2019)
Introduction: “Headache attributed to ingestion or inhalation of a cold stimulus” (HICS) is one of the most common primary headache disorders. Little is known about the pathophysiology of HICS and other headache disorders. The aim of this study was to analyze mean flow velocity (MFV) and cerebrovascular resistance (RI) in both middle cerebral arteries (MCA) upon ingestion of ice water. Methods: The MFV and RI in both MCAs was continuously measured by transcranial sonography. HICS was induced by drinking 200 ml of ice water. Results: In all volunteers, the ingestion of ice water led to a decrease in RI, which was accompanied by an increase in MFV. In volunteers with induced HICS, MFV were significantly higher compared to volunteers that did not experience HICS. In volunteers with HICS, MFV increased even more significantly when lacrimation occurred compared to volunteers in which it did not. In volunteers without induced HICS, MFV was higher in those volunteers with a positive history of HICS than in those with a negative HICS history. Conclusion: This study revealed a raised MFV upon ingestion of ice water. Volunteers with a provoked case of HICS had a higher MFV than volunteers without HICS. The increase in MFV was even higher when the headache was accompanied by lacrimation. This may indicate an involvement of the trigeminal-parasympathetic vasodilator reflex.